The Value of the Intangible in Institutions of Higher Education: a focus on human capital - Moura, Simone Faria (2007)
Higher Education Institutions (HEI) are making an effort to maintain their position on the marketplace within today’s competitive environment. In this context, it is understood the necessity to attribute more value to teaching staff, through the use of relevant resources in intangibles assets. Therefore, it is natural that organizations shall begin to develop policies for Intellectual Capital management, what is to say of its Human Capital. Thus, it was decided to carry out this research with the purpose of surveying about Human Capital management in public and private HEI in Fortaleza. This research is qualitative, and is characterized as an exploratory description, beginning with a desk research study, followed by a survey research with interview and questionnaire applied. The results of this research, indicates that the considerations of majority of HEI managers about the importance to Human Capital and to the correct method to measure the return of investments on it. In despite of these facts, the actual policies adopted by HEI do not consider concrete actions to define the criteria that could enable the Human Capital management.Key-words: Human capital. Intellectual capital. Higher education institutions (HEI).